Low-Fidelity Simulator for the Standardized Training of Fetoscopic Meningomyelocele Repair. Issue 1 (January 2018) - Belfort, Michael A.; Whitehead, William E.; Bednov, Andrey; Shamshirsaz, Alireza A.
Abstract : BACKGROUND: Fetoscopic meningomyelocele repair in a gas-filled uterus is a new technique performed in very few centers. There are few opportunities as well as ethical prohibitions on the initial development and subsequent refinement of innovative fetal surgery techniques in humans, and using an animal model is both very expensive and logistically difficult. METHOD: We developed a low-fidelity endoscopic fetal surgery simulation using a plastic doll and pieces of chicken breast to simulate a fetal meningomyelocele, and a polyurethane ball to simulate a gas-filled uterus, along with a standard endoscopy system and instruments. EXPERIENCE: A unique two-port technique with significant differences from the standard laparoscopic surgery procedure was developed and refined through an iterative phase into a standardized methodology, and the simulator was then used to train three other teams to perform standardized fetoscopic meningomyelocele repair. CONCLUSION: A low-fidelity fetoscopic surgery simulator is a useful tool for developing new fetoscopic operations and for training multidisciplinary fetal surgery teams without the need for extensive use of an animal model. This simulator may be used to further explore the human uterus as a new surgical space for additional fetal surgeries. Abstract : A fetal surgery simulator was built and used to develop and refine the technique and skills in fetoscopic meningomyelocele repair.